The Influence of Financial Literacy, Financial Attitude and Financial Management on Pension Fund Planning in Sleman Regency - Jualian Sundari; Nilmawati Nilmawati (Journal of International Conference Proceedings, 2024)
The process of allocating funds to prepare for future life in order to ensure wellbeing in old age is known as financial planning for retirement. To do that, one must understand the factors that should be taken into account while creating a retirement account. The purpose of this research is to ascertain how financial management, financial attitude, and financial literacy affect Sleman Regency's community retirement fund planning. Convenience sampling was the method of sample, and up to 100 respondents who lived in Sleman Regency were used. This study employs a quantitative methodology, using primary data gathered via a trustworthy and validated questionnaire. This study use multiple linear regression analysis as its data analysis strategy.The study's findings demonstrate the beneficial and noteworthy impact that financial management and literacy have on Sleman Regency's community retirement fund planning. Retirement fund planning, however, is unaffected by one's financial outlook